Miscellaneous observation on Fissidens in Thailand with five new species records - Wongkuna K. (2014)
Five new records of Fissidens for the Thailand moss flora are reported, namely Fissidens flaccidus, Fissidens involutus, Fissidens jungermannioides, Fissidens incognitus and Fissidens serratus. Of these, Fissidens jungermannioides and Fissidens incognitus are new records also for Indochina. Two nomenclatural synonyms are proposed: F. papillulosus Broth. is a new synonym of F. cernulatus Mitt, and F. excedens Broth. is synonymized with F. taxifolius Hedw. Fissidens subspathulatus Dix. is excluded from the Thai moss flora, while F. laxitextus Broth. ex Gangulee is shown to be a perichaetial-limbate species not related to F. pellucidus group. © 2009 Adac. Tous droits réservés.